Design of a Digital Attendance System Based on Geolocation in the KPU Environment Using the Design Thinking Approach - Pamungkas, R Wisnu Prio; Putra, Hamzah Jaya (ASIAN PUBLISHER, 2025)
The digital attendance system based on location serves as a modern solution to improve efficiency, accuracy, and transparency in employee attendance recording in the KPU environment. Using GPS technology and integration with the employee system, this system replaces conventional methods that rely on physical devices and enables real-time attendance via mobile devices. This research aims to design a location-based attendance information system using the Design Thinking approach as a development method. The process includes identifying user needs (employees, HR Bureau admins, and IT managers), developing system flow, prototype development, and simulating the system's functionality. The design results show that this system supports work mobility, reporting accuracy, cross-office integration, and is suitable for supporting flexible work models such as WFH and WFA.